Diagnostic Value of Two-Dimensional Transvaginal Ultrasound Combined with Contrast-Enhanced Ultrasound in Ovarian Cancer - Hu, Rong; Shahai, Gulina; Liu, Hui; Feng, Yuling; Xiang, Hong (Frontiers in Surgery, 2022)
Objective: Explore the value of two-dimensional transvaginal ultrasound combined with contrast-enhanced ultrasound in the differential diagnosis of ovarian cancer, so as to provide the basis for clinical diagnosis and treatment of ovarian cancer. Methods: A total of 62 patients with ovarian cancer who were admitted to our hospital from January 2019 to December 2021 were selected as the research subjects (ovarian cancer group), and 38 patients with benign ovarian tumors in the same period of time were randomly selected as the control (benign group). Two-dimensional vaginal ultrasound and contrast-enhanced ultrasound were performed in both groups. The differences in PI, RI, EDV, PSV, and VM parameters of the two groups as well as those of patients with ovarian cancer of different grades were compared. Results: The PI and RI of the ovarian cancer group were lower than those of the benign ovarian tumor group, and the EDV, PSV and VM of the ovarian cancer group were higher than those of the benign ovarian tumor group (P<0.05). The PI and RI of the patients in stage Ⅰ-Ⅱ of the ovarian cancer group were higher than those in stage Ⅲ-Ⅳ, and the EDV, PSV and VM were lower than those in the patients in stage Ⅲ-Ⅳ, with statistical significance (P<0.05). The results of contrast-enhanced ultrasound showed that the AT and TTP values in the ovarian cancer group were significantly shorter than those in the benign group, and the peak intensity was significantly higher than that in the benign group, and the differences were statistically significant (P<0.05). The sensitivity, specificity, positive predictive value, negative predictive value and accuracy of two-dimensional ultrasound combined with contrast-enhanced ultrasound in the diagnosis of ovarian cancer were high, 95.16%(59/62), 86.84%(33/38), 92.19%(59/64), 91.67%(33/36) and 92.00%(92/100), respectively. Conclusion: Contrast-enhanced ultrasound to some extent makes up for the deficiencies of conventional ultrasound, is helpful to detect early ovarian cancer, and can be used for the differential diagnosis of small ovarian tumors with difficult two-dimensional ultrasound diagnosis. Two-dimensional ultrasound combined with contrast-enhanced ultrasound can effectively improve the detection rate and differential diagnosis value of ovarian cancer.